Spatial distribution of Chlordanes and PCB congeners in soil in Cedar Rapids, Iowa, USA - MARTINEZ, ANDRES (2011)
Residential soils from Cedar Rapids, Iowa, USA were collected and analyzed for chlordanes and polychlorinated biphenyls (PCBs). This study is one of the very few urban soil investigations in the USA. The chlordanes concentrations ranged from 0 to 7500 ng g(-1) dry weight (d.w.), with a mean and standard deviation of 130 ± 920 ng g(-1) d.w, which is about 1000 times larger than background levels. ΣPCB concentrations ranged from 3 to 1200 ng g(-1) d.w., with a mean and standard deviation of 56 ± 160 ng g(-1) d.w. and are about 10 times higher than world-wide background levels. Both groups exhibit considerable variability in chemical patterns and site-to-site concentrations. Although no measurements of dioxins were carried out, the potential toxicity due to the 12 dioxin-like PCBs found in the soil is in the same order of magnitude of the provisional threshold recommended by USEPA to perform soil remediation.